2022
DOI: 10.3991/ijet.v17i06.27845
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning at the University of Jordan in the Setting of Covid-19 Pandemic from the Students’ Perspectives

Abstract: The study aimed to investigate the reality of distance learning at the University of Jordan in the setting of Covid-19 pandemic from the students’ point of view. The study relied on the descriptive analytical approach, and used questionnaire, which consisted of 60 items, as its study tool to achieve the objectives of the study. The stability of the study tool was confirmed and it was validated. The data was collected from a random sample of 826 students from the University of Jordan. The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Perhaps, the tiring and exhausting experience during videoconferencing influenced these two related variables. Students' negative attitudes and acceptance of online learning have also been recorded [27,28]. Understanding the role of attitudes is important because it may influence the strength of intention and acceptance of videoconferencing platforms in the future [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the tiring and exhausting experience during videoconferencing influenced these two related variables. Students' negative attitudes and acceptance of online learning have also been recorded [27,28]. Understanding the role of attitudes is important because it may influence the strength of intention and acceptance of videoconferencing platforms in the future [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Badania kwestionariuszowe dotyczące skuteczności nauki online podczas pandemii COVID-19 wśród studentów i wykładowców prowadzili m.in. Alaghawat i Alshamailah (2022), Asgari i in. (2021), Bahasoan i in.…”
Section: Wprowadzenieunclassified
“…Another study has found considerable heterogeneity in students' preferences for different learning methods [5]. Not every student views online teaching positively [6]. Students' inability to use personal computers, smartphones, and the internet is the most critical factor affecting their online learning [7].…”
Section: Introductionmentioning
confidence: 99%